Molecular identification of Sporothrix species in a hyperendemicarea in Peru - Ramirez Soto, Max Carlos (2021)
To date, there have been no molecular typing studies to identify the Sporothrix species circulating inAbancay, a hyperendemic area of sporotrichosis in Peru. To identify six clinical isolates of the Sporothrixschenckii complex from Abancay, Peru, we used PCR-sequencing of the calmodulin gene, and a phylo-genetic analysis was conducted with these and additional sequences from GenBank. All clinical isolateswere identified as S. schenckii (sensu stricto). Phylogenetic analysis revealed that the six clinical isolatesfrom Abancay, Peru clustered in a clade along with sequences from Costa Rica, Iran, South Africa, and fourother sequences from Peru. These findings reveal the presence of S. schenckii (sensu stricto) in Abancay,Peru.